Prevention and correction of postdecompression liver dysfunction in obstructive jaundice in experimental animals - M. M. Magomedov; M. A. Khamidov; H. M. Magomedov; K. I. Hajiyev (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2021)
Obstructive jaundice is a complex pathology that significantly complicates surgical interventions and is accompanied by a number of negative consequences. In connection with the danger of obstructive jaundice, it is very important to timely identify the severity of this condition and take appropriate measures to treat the patient. To date, methods for predicting the risk of postoperative complications in obstructive jaundice are being actively developed, and methods for treating this pathology are being developed. In this study, we studied the biochemical parameters of the functional state of the liver of dogs with simulated obstructive jaundice with different treatment regimens. 3 experimental groups were formed. Control dogs received no treatment. The dogs of the second group underwent decompression of the biliary tract without control of the rate of bile outflow. In animals of the third group, decompression of the biliary tract was carried out and the rate of bile outflow was controlled. As therapy, dogs of this experimental group received Cytoflavin (0.28 ml / kg body weight) and sulodexide (1 ml / kg body weight) under conditions of moderate hypothermia. All animals underwent laparotomy with puncture of the gallbladder and subsequent introduction of a catheter through the cystic duct into the common bile duct. Blood from the portal vein and lymph from the main lymphatic were taken for the analysis of the following biochemical parameters: direct bilirubin, C-reactive protein, alanine aminotransferase, gammaglutamyl transferase and glucose. The concentration of the listed indicators of the functional state of the liver was assessed at different times after the simulation of obstructive jaundice. The results of the study showed that in dogs of all groups, one day after modeling obstructive jaundice, biochemical parameters significantly increase both in the blood of the portal vein and in the lymph of the thoracic lymphatic duct, which is associated with a violation of the functional state of the liver. In animals in which the rate of bile outflow was not controlled, biochemical parameters remained at a high level, which reflected the development of liver failure and reperfusion syndrome. After administration of cytoflavin and sulodexide in moderate hypothermia, dogs showed a decrease in the concentration of biochemical parameters to the control level, which characterizes the normalization of the functional state of the liver. In general, the proposed treatment regimen has shown high efficiency and can be used to correct post-decompression liver dysfunction in dogs with obstructive jaundice. The results of the study are valuable for the development of methods for treating patients with obstructive jaundice and preventing the development of postoperative complications. This article can be informative for specialists in the field of surgery and anesthesiology who are involved in the correction of postoperative complications in patients with obstructive jaundice.